2011
DOI: 10.1038/nature09724
|View full text |Cite
|
Sign up to set email alerts
|

An actively accreting massive black hole in the dwarf starburst galaxy Henize 2-10

Abstract: Supermassive black holes are now thought to lie at the heart of every giant galaxy with a spheroidal component, including our own Milky Way. The birth and growth of the first 'seed' black holes in the earlier Universe, however, is observationally unconstrained and we are only beginning to piece together a scenario for their subsequent evolution. Here we report that the nearby dwarf starburst galaxy Henize 2-10 (refs 5 and 6) contains a compact radio source at the dynamical centre of the galaxy that is spatiall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
324
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(347 citation statements)
references
References 48 publications
21
324
2
Order By: Relevance
“…While optical diagnostics certainly have a role to play, we need to move toward using alternative search techniques and observations at other wavelengths to make further progress (e.g., radio and X-ray; Reines et al 2011;Reines & Deller 2012;Gallo et al 2010;Kamizasa et al 2012). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While optical diagnostics certainly have a role to play, we need to move toward using alternative search techniques and observations at other wavelengths to make further progress (e.g., radio and X-ray; Reines et al 2011;Reines & Deller 2012;Gallo et al 2010;Kamizasa et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…These two dwarf galaxies have BH mass estimates of M BH ∼ 3 × 10 5 M (Filippenko & Ho 2003;Peterson et al 2005; Thornton et al 2008). Reines et al (2011) present multi-wavelength evidence for the first example of a massive BH in a dwarf starburst galaxy, Henize 2-10, which has an irregular central morphology and no discernible bulge. The evidence for an accreting massive BH includes Very Large Array radio and Chandra hard X-ray point sources at the center of the galaxy and clearly separated from the bright H ii regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Reines et al (2011) reported that the nearby dwarf starburst galaxy Henize2-10 harbors a compact radio source at its dynamical center spatially coincident with a hard X-ray source (possibly an 10 6 M accreting black hole). Farrell et al (2009) found the brightest known ultra-luminous X-ray source HLX-1 (see e.g.…”
Section: Introductionmentioning
confidence: 99%